2020
DOI: 10.21037/jtd-20-1716
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiopathological features and prognosis according to genomic alterations in patients with resected lung adenocarcinoma

Abstract: Background: We investigated the clinicoradiopathological features and prognosis according to genomic alterations in patients with surgically resected lung adenocarcinoma. Methods: Patients who underwent surgical resection for pathologic stage I, II, or IIIA lung adenocarcinoma between 2009 and 2016 and for whom results regarding EGFR mutation, ALK immunohistochemistry (IHC), and KRAS mutation were available were included. Clinicoradiopathological characteristics, genomic alterations, and disease-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Babiy et al said that the latest statistics in China in 2017 showed that the number of lung cancer cases was 730,000, the number of deaths was 590,000, and the two figures also topped the list [ 3 ]. Choi et al said that known risk factors for lung cancer include smoking and air pollution, and the incidence of lung cancer is increasing year by year with the increase of tobacco abuse and environmental pollution worldwide [ 4 ]. Blackstone and El-Aini stated that surgical resection is the preferred treatment for early stage lung cancer, and it is mainly treated by a combination of surgery, radiotherapy, and chemotherapy [ 5 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Babiy et al said that the latest statistics in China in 2017 showed that the number of lung cancer cases was 730,000, the number of deaths was 590,000, and the two figures also topped the list [ 3 ]. Choi et al said that known risk factors for lung cancer include smoking and air pollution, and the incidence of lung cancer is increasing year by year with the increase of tobacco abuse and environmental pollution worldwide [ 4 ]. Blackstone and El-Aini stated that surgical resection is the preferred treatment for early stage lung cancer, and it is mainly treated by a combination of surgery, radiotherapy, and chemotherapy [ 5 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous studies of genetic alterations in lung adenocarcinoma manifesting as SSNs, EGFR mutations were the major driver mutations (frequency of 36-89%) (11,(51)(52)(53)(54)(55). The differences in EGFR mutation frequency among these studies may be partly explained by differences in study populations (Asian vs. Caucasian), detection methods (polymerase chain reaction vs. next generation sequencing), and nodule subtypes (pure GGNs vs. PSNs).…”
Section: Genetic Alterations In Lung Adenocarcinoma Manifesting As Ssnsmentioning
confidence: 99%
“…The differences in EGFR mutation frequency among these studies may be partly explained by differences in study populations (Asian vs. Caucasian), detection methods (polymerase chain reaction vs. next generation sequencing), and nodule subtypes (pure GGNs vs. PSNs). Other genetic alterations identified in lung adenocarcinoma manifesting as SSNs included KRAS mutations, HER2 mutations, BRAF mutations, ALK rearrangement, and ROS1 rearrangement ( 11 , 53 - 58 ).…”
Section: Genetic Alterations In Lung Adenocarcinoma Manifesting As Ssnsmentioning
confidence: 99%
See 1 more Smart Citation
“…In subgroup analyses, the median follow-up duration of patients with cLy1, cLy2, cLy3, and cLy4 were 60 , 38 , 16 , and 12 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] months, respectively. The 5-year OS rates of these patients were 54% (95% CI: 38-76%), 35% (95% CI: 23-54%), 12% (95% CI: 4-34%), and 11% (95% CI: 2-71%), respectively (Figure 2B).…”
Section: Follow-up and Overall Survivalmentioning
confidence: 99%